Federative Republic of Brazil : National Road Safety Capacity Review - World Bank (World Bank, Washington, DC, 2016)
As part of a long-term partnership between the World Bank and Brazil, the Federal Government of Brazil sought the World Bank’s assistance to review road safety management capacity in Brazil, building both on past experiences in the country and international best practices. This National Road Safety Management Capacity Review, therefore, was prepared by the World Bank, with the support of the Global Road Safety Facility (GRSF). The primary objective of the review is to evaluate the multi-sectoral capacity of road safety management in Brazil, identifying possible road safety challenges and presenting recommendations to address these challenges. The methodology of the review, in accordance with the guidelines of the World Bank Global Road Safety Facility, focused on examinations of key functional aspects of road safety, including institutions, legislation, financing, information, and capacities at all levels of government and among non-government actors. The review was prepared mainly based on interviews of key road safety stakeholders at the federal, state, and municipal levels, members of parliament, NGOs, and the private sector, in addition to direct inspection of roads and on-road behaviors, and the analysis of published research and reports on road safety. In addition, information and understanding gained from previous reviews of the states of São Paulo, Rio Grande do Sul, and Bahia were also incorporated.